Waqf-based qardhul hassan financing preference in Malaysia: an exploratory study - Hanudin Amin; M. Kabir Hassan; Imran Mehboob Shaikh (Emerald Group Publishing Ltd., 2024)
Purpose – The purpose of this study is to examine donors’ or waqifs’ desire for waqf-based qardhul hassan financing in Malaysia using a maqasid method, where a pragmatic approach is used. Design/methodology/approach – Using judgemental sampling, a total of 275 waqifs participated in this work to identify their preference in donating their money to the facility should it is introduced. Using the developed waqf-based qardhul hassan scale (WAQASCALE), this study examined the preference accordingly. Data were analysed using IBM SPSS 27. Findings – The results obtained were as follows: the first factor considered by the waqifs in donating money was perceived household well-being, followed by perceived recipients’ welfare, perceived mankind benevolence and perceived Muslims’ community security. Research limitations/implications – The authors developed construct items that had generalisability issues as they were at the infancy stage of development among social finance scientists along with the narrow geographical constraint where the actual survey was conducted. Practical implications – The results were useful in giving new guidance to state governments and Islamic banks (IBs) in Malaysia to explore further this sort of facility for the improved well-being of those affected by COVID-19. Besides, sustainable development goals (SDGs), such as poverty, hunger and responsible consumption, among others can be addressed effectively for the mutual well-being of those affected by the health crisis in an effort of combating financial hardships in the meeting of basic needs, at least. The partnership between the state government and IBs could lead to the offered qardhul hassan financing-sourced funding from waqf for reduced financial hardships by needy and poor folks. Originality/value – This study introduced a new WAQASCALE in the context of qardhul hassan financing in Malaysia